The Representation of Peace Values in The Indonesian ELT Textbook Entitled â€œThink Globally Act Locallyâ€ for the Ninth Grade. - Ardiansyah, Rijalul Zidane; Andayani T, Made Adi; Suharjito, Bambang (English Education Study Program, 2024)
The purpose of this study was to find out how the value of peace was represented and also what was the most dominant value of peace in the Junior High School English textbook entitled